Q: What is the simplified version of 6b plus 3b plus 8b?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b

6+7a+6b

6b^2 - 3b / 3b 6b^2 - 1 or ( 6b^2 - 3b) / 3b = 2b - 1 Or (6b^2 - 3b ) / 3b = 3b(2b - ) / 3b = 2b - 1

3b+6b=9b

12a + 6b + 6c = 6(2a + b + c)

Related questions

add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b

6+7a+6b

6b^2 - 3b / 3b 6b^2 - 1 or ( 6b^2 - 3b) / 3b = 2b - 1 Or (6b^2 - 3b ) / 3b = 3b(2b - ) / 3b = 2b - 1

3b+6b=9b

7 + 4b + 3b + 6b + 5 =7 + 13b + 5 =12 + 13b

5b - 3 - 2b = 6b - 3 3b - 3 = 6b - 3 3b - 6b = 3 - 3 b = 0

12a + 6b + 6c = 6(2a + b + c)

2 x (2a + 3b - 6)

if you mean a^5*3b^9*6a^1, the simplified form is 18a^6b^9

b3 - 5b2 + 12 = (b - 2)(b2 - 3b - 6)Check:(b - 2)(b2 - 3b - 6)= b(b2 - 3b - 6) - 2(b2 - 3b - 6)= b3 - 3b2 - 6b - 2b2 + 6b + 12= b3 - 5b2 + 12

With the assumption your asking what a or b are in terms of each other. a=3b/(6b-2) b=2a/(6a-2)

2a+2b+3a+3b+a+b= 6a+6b 2a+3a+a=6a 2b+3b+b=6b